Analisis Artistik dan Liturgis(Kolaborasi Paduan Suara dan Ansambel Musik Gereja di Jemaat GKI Ebenhaezer Sentani) - Nelinio Parinussa; Ambar Sulistyowati (Institut Agama Kristen Negeri Palangka Raya, 2026)
This study examines the collaboration between choirs and music ensembles in worship at the Ebenhaezer Sentani GKI Church, which is understood as an essential part of the church's liturgical structure. This study aims to identify the artistic characteristics of this collaboration, evaluate its alignment with liturgical needs, and interpret its meaning for music ministers and congregations. The research applies a qualitative approach with a phenomenological design. Data were obtained through semi-structured interviews, observations of the rehearsal process and worship implementation, as well as documentation review in the form of scores and recordings. The research informants consisted of the conductor, choir members, ensemble players, pastors, council, and congregation. Data analysis was carried out through the stages of reduction, presentation, and systematic conclusion drawing using triangulation to ensure the validity of the findings. The findings show that musical collaboration is designed and implemented in a structured manner in worship services. The arrangement of tempo, dynamics, harmony, and rhythm is directed to support liturgical meaning while encouraging congregational participation. The role of the conductor is central in maintaining artistic unity and coordination of the service. Overall, this collaboration contributes to strengthening the atmosphere of worship, fostering solidarity among music ministers, and reinforcing the identity and spiritual experience of the congregation.